An accurate method to obtain bio-metric measurements for three dimensional skull - Hameed, Shihab A.; Zaidan, B. B.; Zaidan, A. A.; Naji, Ahmed Wathik; Tawfiq, O. F. (Asian Network for Scientific Information, 2010)
The goal of this study is to investigate and evaluate how far three-dimensional skull biometric is reliable in term of the accurate measurements, capability and applicability. It was hard to evaluate or simulate an application use three-dimensional skull in biometric, however, can field imaging systems provide a new suitable environment to simulate a new three-dimensional skull biometric. The second goal of this study is to assess how good the new three-dimensional image system is. Subsequently, this study will evaluate the reliability and dependability of using skull biometric. The simulation based on the three-dimensional skull recognition using three-dimensional matching technique. The feature of the simulate system shows the capability of using three-dimensional matching system as an efficient way to identify the person through his or her skull by match it with database, this technique grantee fast processing with optimizing the false positive and negative as well.